Pengaruh Sholawat Nariyah dan Sya’ir Abu Nawas Terhadap Kecemasan Pada Pasien Sectio Caesarea Dengan Spinal Anestesi di RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Karina, Yuni; Tri Yudono, Danang; Suandika, Made (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Sectio caesarea is at risk of complications, one of which is anxiety, anxiety in Sectio Caesrea patients is reported to reach 60% to 92%. One way to overcome anxiety is with sholawat nariyah and sya'ir abu nawas. Objective: to determine the effect of sholawat nariyah and sya'ir abu nawas on anxiety in Sectio Caesarea patients with spinal anesthesia. Method: This research is quantitative with Pre-experiment research design with one group pretest-posttest. The study population was all Sectio Caesarea patients with accidental sampling technique totaling 35 respondents. The research was conducted on July 09-21, 2024 at RSUD Dr. The research instrument used The Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire followed by statistical analysis using the Wilcoxon test: Before listening to sholawat nariyah and sya'ir abu nawas, 25 respondents (71.4%) experienced moderate anxiety. After listening to sholawat nariyah and sya'ir abu nawas, 25 respondents (71.4%) experienced mild anxiety. Wilcoxon test showed that sholawat nariyah and sya'ir abu nawas had a significant effect on reducing anxiety scores. As well as a significance value of 0.000 and ? value less than 0.05. Conclusion: there is an effect of sholawat nariyah and sya'ir abu nawas on anxiety scores.